Pasteurella multocida pneumonia complicated by Staphylococcus aureus. Issue 700 (February 1984) - Martyn, V.; Swift, D.
Abstract : A 71-year-old woman presented with acute non-cardiogenic pulmonary oedema. She proved to have a Pasteurella multocida pneumonia, with blood stream invasion by the organism, and required positive pressure ventilation for 53 days. Penicillin G., the drug of choice for this infection, failed to reverse the steady decline in her arterial oxygen-tension, and it was only after treatment with chloramphenicol and prednisolone that she began to improve. Serological tests strongly indicated the presence of a Staphylococcus aureus infection and the delay in giving antibiotics appropriate to this second pathogen may have been the reason for the patient's initial downhill course.